1999
DOI: 10.1161/01.res.85.5.394
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor Activators Inhibit Thrombin-Induced Endothelin-1 Production in Human Vascular Endothelial Cells by Inhibiting the Activator Protein-1 Signaling Pathway

Abstract: Endothelin-1 (ET-1), a 21-amino acid vasoactive peptide mainly produced by vascular endothelial cells, is involved in the regulation of vascular tone and smooth muscle cell proliferation. Peroxisome proliferator-activated receptors (PPARs), key players in lipid and glucose metabolism, have been implicated in metabolic disorders that are predisposing to atherosclerosis. Because of the potential role of ET-1 in vascular disorders such as hypertension and atherosclerosis, we investigated the regulation of ET-1 ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
325
3
7

Year Published

1999
1999
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 480 publications
(349 citation statements)
references
References 48 publications
14
325
3
7
Order By: Relevance
“…The expression of eNOS and endothelin-1 is known to be coordinately regulated in diverse pharmacological and experimental conditions. 45,46 Since PPAR␣ agonists have the potential to inhibit endothelin-1 expression, 10 our results may give another example of the coordinated regulation between eNOS and endothelin-1 systems. These effects might explain the vasodilator function of PPAR␣ agonists.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The expression of eNOS and endothelin-1 is known to be coordinately regulated in diverse pharmacological and experimental conditions. 45,46 Since PPAR␣ agonists have the potential to inhibit endothelin-1 expression, 10 our results may give another example of the coordinated regulation between eNOS and endothelin-1 systems. These effects might explain the vasodilator function of PPAR␣ agonists.…”
Section: Discussionmentioning
confidence: 73%
“…[3][4][5] Such effects may be attributable at least in part to their effects on lipoprotein abnormalities, which are mainly exerted by PPAR␣ expressed in the liver. Several studies 9,10,17,18 have demonstrated that PPAR␣ is also expressed in vascular endothelial cells. Recently, direct roles of fibrates in vascular endothelial cells have become evident, clarifying the inhibitory effects of the PPAR␣ activators on the expression of VCAM-1, IL-6, and endothelin-1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vascular endothelium, PPAR␥ functions to increase Cu/Zn superoxide dismutase 33 and plasminogen activator inhibitor-1 expression 8 and inhibit cytokine-induced monocyte chemotactic protein-1 production, 34 leukocyte-endothelial interactions, 10 angiogenesis, 11 and thrombin-induced endothelin-1 production. 9 Taken together, these reports suggest that PPAR␥ plays an important role in endothelial biology and the pathogenesis of vascular disease.…”
Section: Discussionmentioning
confidence: 90%
“…There are a number of reports that describe transrepression on gene expression by PPAR␣ through interference with NF-B signaling pathway, including but not limited by cytokine-induced vascular cell adhesion molecule-1 (45) and endothelin-1 (46). Furthermore, PPAR␣ ligands repress acute phase proteins such as fibrinogene (47).…”
Section: Discussionmentioning
confidence: 99%